The Impact of Inflation on Bank Risk: A Study of Islamic Banks - Isni Andriana; Anna Yulianita; Yos Karimudin; Kemas Muhammad Husni Thamrin; Muizzuddin Muizzuddin (Faculty of Economics, Universitas Sriwijaya, 2023)
Risk is the one thing that the financial system anticipates more than any other issue. In 2001, a failure in bank risk management occurred at Bank Imar in Turkey, which led to losses that reached around 7.2 billion due to shareholder corruption and coordinated criminality (Mukminin, 2018). The research objective is to investigate the extent to which inflation and business risk are related in Islamic banks operating in the 26 countries covered in the study. Based on the findings of this study, it can be concluded that the inflation proxy does not, in any meaningful sense, have a constructive effect on inflation. That is to say, the business risk in Islamic banks will not be affected in any way by any changes that take place in inflation, regardless of whether those changes result in a rise in value or a loss in value. The use of variable proxies will likely result in some limitations being imposed on this study, which will, in turn, have an effect on the conclusions of the research. In following research, macroeconomic indicators like gross domestic product (GDP) and exchange rates could potentially serve as test subjects for examination.